Privat oder Staatlich? Automobile Konsumkultur in der Sowjetunion, der DDR und Rumänien - Gatejel, Luminita (Comparativ, 2009)
Private or State-Owned? Automobile Consumer Culture in the Soviet Union, the GDR, and Romania The article teases out the common features of a socialist consumer culture by taking three different national settings under scrutiny. Central to the inquiry is the automobile as one of the most prestigious artifacts in the Soviet Union, East Germany and Romania. The main contentious issue regarding the status of the automobile was whether cars should be awarded by the state to its most loyal citizens, bought freely, or rented from state companies. The exclusivist Stalinist consumer society was radically transformed in the postwar period due to internal political reconfiguration and the influence of the other block countries. This comparative study has shown that between Moscow and its satellites a vivid cultural exchange took place that coined the automobile culture of the last decades of socialism. The silent partner in this exchange was the West that made mass motorization around the private car its main characteristic also under socialism.